DIFFERENCES OF LEAVES SAMBILOTO (Andrographis paniculata Sp) EXTRACT ON THE PERFORMANCE AND MORTALITY OF LAYING BREED CHICKEN ON STARTER PHASE - Mohammad Asrofi; Nita opi Ari Kustanti; Risma Novela Esti (Universitas Islam Balitar, 2021)
The purpose of this study is to know the difference of sambiloto leaves (Andrographis paniculata Sp) extract on mortality and performance of the starter phase laying hens. Two hundred and forty laying hens (ages 1-6 weeks) were used in this experiment. It is divided into 4 groups and 6 replays. Treatment is divided into control P0, P1 + 2 gr / kg feed, P2 + 4 gr / kg feed and P3 6gr / kg feed. The observed variables are Mortality, Feed Consumption, Feed Weight Growth and Feed Conversion. Real different Mortality (P>0.05) increased to 10.7037 (P0,P2 and P3) while decreased compared to 10 (P1). Feed Consumption differed very noticeablely (P>0.01) decreased to 8,908 gr/ecr (P3) compared to control (P0), as did 9,438 gr/ecr (P1) and 9,550 gr/ekr (P2). Weight Growth is not affected by treatment (P>0.05). It is very different Feed Conversions (P>0.01) decreased to 3,684 (P3) compared to 4,003 (P2) as well as 3,956 (P0) and 3,978 (P1). There needs to be more research done from the sterter phase to the grower phase in order to know the further influence